2012
DOI: 10.5012/bkcs.2012.33.8.2483
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Kinetics and Mechanism of Grain Growth during the Thermal Decomposition of Magnesite

Abstract: The X-ray line broadening technique was used to calculate the grain size of MgO at 1023, 1123, 1223 K respectively either in CO 2 or during the thermal decomposition of magnesites in air as well as in vacuum. By referring to the conventional grain growth equation, D n = kt, the activation energy and pre-exponential factor for the process in air are gained as 125.8 kJ/mol and 1.56 × 10 8 nm 4/s, respectively. Ranman spectroscopy was employed to study the surface structure of MgO obtained during calcination of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…[12] in which the two low-lying isomers were found not to be C 1 and D 4h in sequence. The hybrid structure C s for (MgO) 5 has not been mentioned in Ref. [12].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[12] in which the two low-lying isomers were found not to be C 1 and D 4h in sequence. The hybrid structure C s for (MgO) 5 has not been mentioned in Ref. [12].…”
Section: Resultsmentioning
confidence: 99%
“…For (MgO) 4 , stair-type fused rhombi (C 1 ) becomes easier to gather than octagonal rings structure D 4h . For (MgO) 5 , fused rhombi structure C 1 and hybrid structure C s become easier to assemble than ten-member ring structure D 5h . The lowest-energy structure of (MgO) 6 becomes the distorted cubic structure (D 2h ) instead of the stacked double ring structure (D 3d ).…”
Section: Growth Strategies Of (Mgo) N Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Razouk et al 28 reported that water vapor accelerates sintering of magnesia. Fu et al 29 studied the surface structure of MgO and reported that steam results in growth of the MgO grains during calcination of magnesite. Therefore, it is logical to assume that the presence of steam during dolomite decomposition may sinter the produced MgO in the product layer and results in larger pores that facilitate the outward movement of produced CO 2 , resulting in lower partial pressure of CO 2 in the sample.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…They obtained a result that the one-step Mg reduction production process can reduce reduction time and save energy [10][11][12][13]. Fu et al studied the thermodynamics and kinetics of the integration process of calcination and reduction and found that canceling the calcination process can greatly save energy [14][15][16][17][18]. These studies rely on reducing calcination to achieve continuous production of Mg. Other researchers used an inert gas to replace the vacuum state.…”
Section: Introductionmentioning
confidence: 99%